Mediating anion-cation interactions to improve aqueous flow battery electrolytes. (August 2022) - Reber, David; Thurston, Jonathan R.; Becker, Maximilian; Pach, Gregory F.; Wagoner, Marc E.; Robb, Brian H.; Waters, Scott E.; Marshak, Michael P.
Highlights: - Enhanced solubility for a wide variety of metal-organic chelates. - Electrolyte capacity of 40 Ah L −1 at near neutral pH. - Discharge power densities >400 mW cm −2 . - Enhanced solubilization power for more acidic anion-receptors. - Easily transferrable approach to other active materials. Abstract: The limited solubility of electrolyte active materials has impeded the development of energy dense aqueous redox flow batteries. Here, we report on the solubilizing effect urea has on metal-organic complexes chelated by aminopolycarboxylate ligands. Upon addition of urea, solubility enhancements of up to 60% or 125% are observed for chromium ethylenediaminetetraacetate (CrEDTA) and chromium 1, 3-propylenediaminetetraacetate (CrPDTA) salts, respectively, resulting in maximum solubilities of e.g., 1.5 м for KCrPDTA and 2.2 м for NaCrEDTA. We investigate the mechanism behind enhanced solubility of aminopolycarboxylate chelates, revealing strong hydrogen bonding between urea and anions, resulting in eutectic-like destabilization of the solid phase. We study the impact of urea on the electrochemical performance of near neutral pH flow batteries and demonstrate 50% higher anolyte capacities, up to 40 Ah L −1, than previously reported for this promising class of materials. In capacity balanced full cells, using ferrocyanide catholytes, we observe excellent Coulombic efficiencies >99.6% and voltage efficiencies >78% at average discharge voltages of ca. 1.5 V when cycling at 100 mA cm −2 . Peak discharge power densities of >400 mW cm −2 further highlight the potential of our facile and cost-effective approach. Finally, we discuss avenues for future work to further exploit the solubilizing effect described herein. Graphical abstract: Image, graphical abstract